DETERMINAN MANAJEMEN LABA: KAJIAN EMPIRIS PADA PERUSAHAAN MANUFAKTUR GO PUBLIK DI BURSA EFEK INDONESIA - Eny Kusumawati (Riset Akuntansi dan Keuangan Indonesia, 2019)
This study aimed to analyze the effect of nonfinantial and finantial to earnings management companies are included in the manufacturing company listed on the Indonesia Stock Exchange for the period 2014 until 2016. The finantial included leverage, free cash flow, profitability, tax planning, firm size and nonfinantial included managerial ownership, institutional ownership, independent board of commissioner, audit committee, audit quality. Measuring the earnings management used a discreationary accrual model. There were 120 companies taken by purposive sampling. Data was analyzed using multiple linear regression. Result of the data analysis showed that managerial ownership, institutional ownership, independent board of commissioner, and tax planning had no significantly effect on the earnings management. The audit committee, leverage, free cash flow, profitability, audit quality and firm size had significantly effect on the earnings management.  Keywords: finantial, non finantial, earning management